2013
DOI: 10.1016/j.athoracsur.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Assist Device Implant in the Elderly Is Associated With Increased, but Respectable Risk: A Multi-Institutional Study

Abstract: Background There are an increasing number of elderly patients with end-stage heart failure. Destination mechanical circulatory support is often the only therapy available for these patients who are not transplant candidates. The outcomes after continuous flow left ventricular assist device (CF LVAD) implant in older patients remains unclear. We undertook this multi-institutional study to quantify short-term and midterm outcomes after CF LVAD implant in the elderly. Methods We retrospectively analyzed all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 24 publications
1
51
0
Order By: Relevance
“…MCS is also being used increasingly as a bridge to transplant or, more commonly in older patients, as destination therapy. 202 Although some older patients benefit from MCS, 203 the risk of complications, including gastrointestinal bleeding, stroke, and infections, increases with age. 202 In addition, very few patients $80 years old have been treated with MCS, so the value at very elderly ages is unknown.…”
Section: Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCS is also being used increasingly as a bridge to transplant or, more commonly in older patients, as destination therapy. 202 Although some older patients benefit from MCS, 203 the risk of complications, including gastrointestinal bleeding, stroke, and infections, increases with age. 202 In addition, very few patients $80 years old have been treated with MCS, so the value at very elderly ages is unknown.…”
Section: Older Adultsmentioning
confidence: 99%
“…202 Although some older patients benefit from MCS, 203 the risk of complications, including gastrointestinal bleeding, stroke, and infections, increases with age. 202 In addition, very few patients $80 years old have been treated with MCS, so the value at very elderly ages is unknown. Similarly as for all patients, consideration of MCS in older patients as destination therapy should be undertaken only after detailed discussion of the risks, benefits, and alternatives, including palliative care and hospice.…”
Section: Older Adultsmentioning
confidence: 99%
“…In fact, the current growth of the DT CF-LVAD population 14 can be expected to rise in light of recent studies reporting successful outcomes in more elderly patients. [17][18][19] Understandably, such expansion into more geriatric cases may further limit HMRS validity.…”
Section: Discussionmentioning
confidence: 96%
“…34 Using the largest allpayer database in the United States, Kilic et al 35 observed comparable mortality, with no independent impact of age on inpatient mortality, when comparing elderly patients (age > 70, n=1,472) to a younger group (age 60-69, n=2,787) supported with continuous-flow LVAD. Somewhat contradictory data was published by Atluri et al, 36 who examined the INTERMACS national registry from 2006 to 2012 and similarly dichotomized patient groups into age > 70 (n=590) and age < 70 (n=4,439). They found that despite higher INTERMACS profiles (indicating less severe illness at time of enrollment), comparable heart bypass time and comparable length of stay, 2-year survival was lower in the older cohort (63% vs 71%, P<0.001).…”
Section: Left Ventricular Assist Device Therapymentioning
confidence: 97%